Novels Ancika Dia Yang Bersamaku Tahun 1995 by Pidi Baiq in Feminist Perspective - Iqbalva Demas Wibowo; Onok Yayang Pamungkas (Athena: Journal of Social, Culture and Society, 2023)
This study represents an effort to investigate the feminist spirit within Pidi Baiq's novel "Ancika Dia Yang Bersamaku Tahun 1995". The study employs a qualitative research method. The data used is the novel Ancika Dia Yang Bersamaku Tahum 1995, published by Pastel Books in 2021. Data collection was carried out through the technique of note-taking. The findings of the study reveal that the novel Ancika Dia Yang Bersamaku Tahun 1995 possesses a strong representation of feminism. Through the story's plot, the author presents a discourse about the equality of rights and obligations between women and men. The novel portrays the importance of equality, equal rights, and respect for women. Through the character of Ancika, readers are invited to witness the role of a strong, brave woman who is capable of determining her own fate. This stimulates thought about the importance of creating a just and inclusive society, where women have an equal and respected role in all aspects of life. The implications of the findings highlight the importance of valuing and recognizing the equality between women and men in various aspects of life. Thus, society must strive to create an environment that is fair and inclusive, where women have equal rights with men in social interactions, relationships, and other fields.